Analisis Semiotika Terhadap Prosesi Pernikahan Adat Jawa “Temu Manten” di Dolok Ilir I Kecamatan Dolok Batu Nanggar - Sri Nurhayati; Ahmad Fadlan; Ainul Hakim Syukri; Hassan Sazali; Maulana Andinata Maulana Andinata (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to determine and analyze the meaning of the Javanese traditional wedding